Polyoxometalate catalyzed ozonation of chemical pulps in organic solvent media - Shatalov, Anatoly A. (2015)
Polyoxometalate (POM) catalyzed ozonation of chemical pulps in organic solvent media was found to be particularly effective and selective environmentally benign bleaching approach providing a way for substantial increase in pulp brightness, viscosity and degree of delignification in comparison with other ozone-based bleaching techniques. A series of tested low-boiling polar aprotic and protic organic solvents showed awell-defined capacity for ozonation improvement in the presence of Keggin-type heteropolyanion [PMo7V5O40]8− (HPA-5). Even moderate solvent proportion of 6% (w/w) in the reaction solution caused additional gain in brightness up to 3.4% ISO with simultaneous increase in pulp viscosity up to 8.8% and lignin removal up to 18.9% after HPA-5 catalyzed ozonation (0.8% O3; 0.5mMHPA), as compared with the control solvent-free process. An aqueous acetone solutionwas found to be the preferred reaction medium in terms of pulp brightening and delignification. Under optimized conditions, the POM-catalyzed ozonation of eucalypt kraft pulp in acetone/water solution showed remarkable brightness improvement by 15.1% ISO with additional lignin removal by 39.4% and increase in intrinsic viscosity by 3% in comparison with pulp bleached in water media